2005
DOI: 10.1016/j.clim.2005.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Undetectable serum IgA and low IgM concentration in children with congenital hypothyroidism

Abstract: Some studies suggest thyroid hormones may regulate the human immune system. In order to evaluate the effect of thyroid hormone deficiency on antibody production, we evaluated serum IgA and IgM concentrations in 83 children with congenital hypothyroidism (CH), diagnosed by neonatal screening. Patients were compared to two healthy, age-matched control groups. Patients with permanent CH had a significantly higher frequency of undetectable IgA concentrations (thyroid agenesis, P < 10 À5 ; thyroid ectopy, P = 0.013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In line with this, reduced total BM cell numbers have been demonstrated in T3Rα −/− mice, and thyroid hormones have been found to stimulate pro-B lymphocyte proliferation, thereby increasing total numbers of B lymphocyte progenitors [36,49]. Moreover, hypothyroidism in humans is also associated with decreased bone marrow output [50]. Based on these data we hypothesized that increased thyroid hormone levels in GD influence bone marrow activity and thereby contribute to the increased transitional and pre-naive B lymphocyte numbers that we found in the peripheral blood from GD patients.…”
Section: Discussionmentioning
confidence: 72%
“…In line with this, reduced total BM cell numbers have been demonstrated in T3Rα −/− mice, and thyroid hormones have been found to stimulate pro-B lymphocyte proliferation, thereby increasing total numbers of B lymphocyte progenitors [36,49]. Moreover, hypothyroidism in humans is also associated with decreased bone marrow output [50]. Based on these data we hypothesized that increased thyroid hormone levels in GD influence bone marrow activity and thereby contribute to the increased transitional and pre-naive B lymphocyte numbers that we found in the peripheral blood from GD patients.…”
Section: Discussionmentioning
confidence: 72%
“…On the other hand, ATDs transmitted through the placenta or milk have been shown to expose the fetuses/neonates to a risk of hypothyroidism [2]. The disruption of perinatal thyroid function causes disorders in many networks, including the central nervous system [3] and the immune system [4]. In addition, previous studies have revealed that certain flame retardants might act on the developing thyroid system [5], suggesting that some environmental contaminants may modulate the balance of these thyroid function-related networks [6].…”
Section: Introductionmentioning
confidence: 99%
“…Data from hypothyroidism in humans [31] , or experimentally induced hypothyroidism in rodents, have been shown to diminish thymic activity, effects that were reversed by treatment with thyroid hormones [32] . In addition, hypothyroid experimental conditions lead to spleen and lymph node involution, as well as to depressed humoral and cell-mediated immune responses [33,34] .…”
Section: Consequences Of Aitd Endocrine Alterations On Immunitymentioning
confidence: 99%